DOES GOOD CORPORATE GOVERNANCE AND FINANCIAL RATIO ABLE TO PREDICT FINANCIAL DISTRESS? STUDY ON PUBLIC COMPANIES IN ENERGY AND RAW MATERIALS SECTOR - Clairine Angelica Riona Saputra; Tan Ming Kuang (Universitas Katolik Indonesia Atma Jaya, 2022)
For investors and creditors, the sustainability of an entity's business is an important matter, so that information about financial distress becomes significant in determining investment decisions and loans. Measuring the effect of good corporate governance mechanisms and financial ratios on business sustainability is the aim of this study. The sample includes 174 data on energy and raw material sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period which are accessed using the refinitive database and the Indonesian stock exchange. Using logistic regression, this study finds that those that have no effect on financial distress are independent commissioners, liquidity ratios, and leverage ratios, while those that have a negative effect on financial distress are managerial ownership, institutional ownership, and profitability ratios. This finding implies the significance of profitability as a predictor of financial distress and institutional ownership and management in determining business sustainability.